MicroRNAs as Novel Biomarkers in Colorectal Cancer - Glavac, Damjan; Hrasovec, Sonja (Frontiers in Genetics, 2012)
MicroRNAs (miRNAs) play an important role in various physiologic and developmental processes and in the initiation and progression of cancer. This class of small, non-coding RNAs critically regulate gene expression at the post-transcriptional level and evidence suggests that they may function as both oncogenes and tumour suppressors. Colorectal cancer (CRC) is a major healthcare concern worldwide and in order to reduce CRC related deaths, research is aimed into the search for some novel screening approaches. In this sense, miRNAs are rapidly emerging as a novel class of biomarkers, with good potential as diagnostic and therapeutic targets. This review summarizes the recent findings of the clinicopathological relevance that miRNAs have in CRC initiation, development and progress, highlighting their potential diagnostic, prognostic and therapeutic use in CRC, focusing on the group of microsatellite unstable and the group of hypermethylated CRCs, as well as discussing future prospects.